Surgical anatomy for mastery of open operations : a multimedia curriculum for training surgery residents - Jensen, Mark O. (Philadelphia : Wolters Kluwer, 2019)
'In today's surgical environment, open operations have declined in frequency, but the need for a practical, superbly illustrated reference in this area is still great. Ideal for both trainee and experienced surgeons, Surgical Anatomy and Mastery of Open Operations: A Multimedia Curriculum for Training Residents achieves this goal with expert coverage of essential open procedures, both common and uncommon. In print and on video, this'go to' resource includes clinical highlights, practical tips, and detailed illustrations'--Provided by publisher.
This book includes online access at http://medicine.lww.com/activate, please refer library staff for the password.
Includes bibliographical references and index.
Online access password : WK2KZCFN4PDR
Keywords: Anatomy, Regional; Surgical Procedures, Operative